2018
DOI: 10.1097/mao.0000000000001934
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Cochlear Length Using Cone Beam Computed Tomography in Adults With Cochlear Implants

Abstract: A novel method for calculating outer- and inner-wall cochlear length using CBCT images has been developed which is feasible in clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 55 publications
0
6
1
Order By: Relevance
“…Gender is another covariate that may affect the size of cochleae, because most related studies found that males' OC was slightly longer than that of females. Certain studies reported that the cochlear size was significantly different between men and women, 2,5,15,19,42,43,57,67 whereas others did not find such a difference 11,12,14,23,28,36,43,59 . This review found no significant difference in the cochlear size according to gender.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…Gender is another covariate that may affect the size of cochleae, because most related studies found that males' OC was slightly longer than that of females. Certain studies reported that the cochlear size was significantly different between men and women, 2,5,15,19,42,43,57,67 whereas others did not find such a difference 11,12,14,23,28,36,43,59 . This review found no significant difference in the cochlear size according to gender.…”
Section: Discussioncontrasting
confidence: 51%
“…In this systematic review, the data were obtained from 56 studies 2–5,11,12,14–17,19,20,22–26,28–30,32–37,39–45,53–74 . However, there were 65 different subgroups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also in 2014, it was shown that outer cochlea wall measurements could be measured on cone beam CT and these measurements fall in a normal distribution [13]. Then in 2018, it was shown that the inner wall could also be measured on cone beam CT [14]. And in 2017, a method for automated two-turn CDL measurements was presented to decrease clinical time spent measuring CDL and to address user-dependent measurement variability [15].…”
mentioning
confidence: 99%